Improving obsessive-compulsive buying through brand attachment and hedonic value: customer-based brand value - Panjaitan, Roymon; Yuswono, Irawan; Afendi, Arif; Ardyan, Elia (Business: Theory and Practice, 2025)
This study aims to explore how hedonic value influences obsessive-compulsive buying behavior by examining the mediating roles of brand attachment and customer-based brand value. The research addresses inconsistencies in previous studies on the influence of hedonic market value on obsessive-compulsive buying by integrating brand attachment and customer-based brand value as key factors. The literature review reveals a gap in understanding the mediating role of these variables in the relationship between hedonic value and compulsive buying. Six hypotheses were developed and tested using PLS-SEM within a sample of 246 customers in Central Java, Indonesia. The results highlight that customer-based brand value significantly mediates the impact of hedonic value on brand attachment, which in turn enhances obsessive-compulsive buying. Additionally, the study finds that brand attachment directly contributes to the increase in compulsive buying behavior. The findings suggest that a positive customer experience, influenced by strong brand identity, is crucial in fostering brand attachment and subsequently driving obsessive-compulsive purchasing. This research provides a comprehensive understanding of how hedonic and brand-related factors interact to influence consumer behavior.